Caregiving experiences of family caregivers of disabled middle-aged and older adults enrolled in long-term care insurance: a qualitative study - Yitong Liu; Wenkun Xu; Zhuoya Yang; Yaning Wang; Rujian Lu; Yuexia Gao; Yaqin Zhong (BMC Nursing)
Abstract Background Long-term care insurance (LTCI) projects were an essential components of health systems designed to support disabled people and their families. Despite LTCI has been getting more and more attention and promotion, there was a lack of qualitative study to explore the experiences of family caregivers who were directly involved in the care of disabled people enrolled in these projects. This study aimed to explore the experiences of family caregivers in the caregiving process within the context of LTCI. Methods This qualitative study used inductive content analysis to explore the experiences of family caregivers of disabled people. Fifteen family caregivers from long-term care service companies and communities in Nantong city were purposively selected to participate in the study between December 2023 to February 2024. Semi-structured in-depth interviews were conducted to collect data. The interviews were audio-recorded and transcribed verbatim. Results The results revealed a total of five major themes with thirteen sub-themes including: (1) caregiver fatigue (i.e. heavy daily care tasks, and lack of rest); (2) emotional stress (helplessness and depression, and isolated and alone); (3) perceived benefits of caregiving (emotional connection, and a new outlook on life); (4) more expectations for LTCI (expect respite care, expect medical care facilities, expect longer service duration and frequency, and expect more economic subsidies); and (5) positive evaluations of LTCI (provide psychological support, reduce the burden of care, and professional care services). Conclusions This study’s findings improved our understanding of caregiving experiences among family caregivers of disabled people enrolled in LTCI. Identifying caregivers’ experiences enabled the authorities to develop support strategies and interventions focused on helping them reduce the caregiver burden.